Mapping evidence on charitable food assistance system’s compliance with safety and general hygiene requirements in Africa and the rest of the world: a systematic scoping review protocol - Sizwe Makhunga; Tivani Mashamba-Thompson; Khumbulani Hlongwana (Systematic Reviews, 2019)
Abstract Background The charitable food assistance system has an influential role in the larger effort to curtail the problem of food insecurity globally. They often play a crucial role in meeting the food security needs of the poor, particularly resource-limited settings where food security is a challenge. The aim of our study is to compare evidence on the safety and general hygiene of charitable food assistance system in Africa and the rest of the world. Methods This study will be conducted through a systematic scoping review. We will search for literature from the following electronic databases: African Index Medicus, PubMed, Google Scholar, EBSCOhost (MEDLINE with full text, Academic Search Complete, MEDLINE) and open access for unpublished theses and dissertations. Articles will also be searched through the ‘Cited by’ search as well as citations included in the reference lists of included articles. Websites, such as the World Health Organization (WHO) and the Departments of Health websites, will be searched for policies and guidelines for food charity practice. Studies will be identified by searching literature published in any language between 1967 and 2018. Then, following title screening, eligible studies will be exported to EndNote library where duplicates will be removed before the parallel screening of abstracts and full articles by two independent reviewers. Screening will be guided by the study eligibility criteria. Data from the included studies will be extracted, and the emerging themes will be analysed. The relationship of the emerging themes to the research question will be critically examined. The quality of the included studies will be determined by the use of Mixed Method Appraisal Tool (MMAT)—version 2011. The search results will be presented through the use of the adapted PRISMA-P chart. Discussion We hope to find relevant studies that highlight evidence of charitable organisations’ food safety and general hygiene practices, in order to effectively compare their performance to those of formal and informal food establishments. Findings of this study will be disseminated electronically, in print and through peer presentation, conferences and congresses on synergies between efforts to reduce food loss and waste and those practices of public health concern.